Corporate culture and health care organization - I Izamin,; M Jamsiah,; I Aniza, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2007)
Each organization has a particular culture, due to personal interactions, with certain values shared by its members. Corporate culture is defined as ‘the set of shared, taken-for-granted implicit assumptions that a group holds and that determines how it perceives, thinks about, and reacts to its various environments’. Positive corporate culture is linked to increased staff alignment, advanced level of employee commitment, increased employee productivity, enhanced organizational effectiveness and increased profitability. Researchers claimed that most studies suggesting the associations between culture and performance are methodologically weak. Cultural transformation has been a big part of NHS reforms and health system redesign in United States to deliver improvements in quality and performance. Environment, market competition, technology advancement, information age and government policies will influence the cultural change within the organization. Undesirable culture might emerge if the organization does not act appropriately to manage its corporate culture. There are six critical success factors for the implementation of corporate culture changes: committed and effective leadership, clear definition of the desired goals, rigorous implementation of a change management model, effective mitigation of change resistance, active governance structure and a design model, and effective communication. Among the issues in implementing corporate culture within healthcare organizations are middle managers dilemma, cultural diversity and subcultures within the organization, size of healthcare organization and critical mass.